Identification and Functional Investigation of Genome‐Encoded, Small, Secreted Peptides in Plants. Issue 3 (5th July 2019) - Boschiero, Clarissa; Lundquist, Peter K.; Roy, Sonali; Dai, Xinbin; Zhao, Patrick X.; Scheible, Wolf‐Rüdiger
Abstract: Hundreds to thousands of small secreted peptides (SSPs) are encoded in plant genomes but have been overlooked, and most remain unannotated and unstudied. Despite their low profile, they have been found to confer dramatic effects on growth and development of plants. With the growing appreciation of their significance, the development of appropriate methods to identify and functionally assess the myriad SSPs encoded in plant genomes has become critical. Here, we provide protocols for the computational and physiological analysis of SSPs in plant genomes. We first describe our methodology successfully used for genome‐wide identification and annotation of SSP‐coding genes in the model legume Medicago truncatula, which can be readily adapted for other plant species. We then provide protocols for the functional analysis of SSPs using various synthetic peptide screens. Considerations for the design and handling of peptides are included. © 2019 by John Wiley & Sons, Inc.